MANAJEMEN STRATEGIS PENGEMBANGAN DESA WISATA NGADIMULYO KABUPATEN TEMANGGUNG - Oryza Lathifatul Ulya; Hesti Lestari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2023)
Ngadimulyo’s Tourism Village is a program that aims to develop tourism potential in Ngadimulyo Village. Papringan Ngadiprono Market provides an opportunity for Ngadimulyo Village to develop tourism potential in other hamlets. There were several problems in the process of developing the Ngadimulyo’s Tourism Village, one of which was the corruption case in tourism financial assistance by the Head of the Ngadimulyo Village, the Secretary of the Ngadimulyo Village, the Former Head of the Ngadimulyo Village, and the Head of the Ngadimulyo’s Tourism Village. This problem creates new problems, such as inactive management and tour packages, and several other problems. This research is a qualitative research that aims to produce a development strategy for the Ngadimulyo’s Tourism Village. This research uses the theory of strategic management and tourism village development as a basis for analyzing the internal and external of Ngadimulyo’s Tourism Village. The analysis of the internal and external environment is then identified and evaluated using analytical tools, the SWOT Matrix (Strength, Weakness, Opportunity, Threat) and Bryson's Litmus Test. Based on the results of this research, it shows that there are four strategic issues for developing the Ngadimulyo’s Tourism Village, including: 1) Developing tourism potential outside the Ngadiprono’s Hamlet; 2) Involving other hamlet communities in the management and development of the Ngadimulyo’s Tourism Village; 3) Improving the financial management of Ngadimulyo’s Tourism Village; and 4) Maximizing coordination with government and the private sector to support the development of the Ngadimulyo’s Tourism Village.